Artista como trabalhador do presente: relações entre trabalho, educação superior e empreendedorismo - Paloma Elaine Santos Goulart (2016)
This study deals with the relationship between higher education, work and entrepreneurship in fields of work that demand knowledge and artistic skills. Three dimensions were analyzed for the development of the theme: 1) labor market, 2) expectations and perceptions of the main agents in the relation of higher education - students and teachers, 3) formal and general regulations, applicable to courses of artistic interface in institutions of higher education. The bases used for analysis were the Census, 2010, the data of the research Entrepreneurs Artists, 2014/2015 and the National Curricular Guidelines of the superior courses regulated by the Ministry of Education of Brazil. The results show that occupations in the artistic fields in Brazil are predominantly informal and that entrepreneurship is a value received by students and professors linked to courses with an artistic interface in a university environment. Being agraduate in higher education can significantly increase income and also influence the achievement of formal jobs. The results strengthen the human capital theory, with some considerations. The thesis constructed is that of the artist as a worker of the present, whose obtaining of jobs and income are strongly influenced by the schooling, as it happens for the occupations in general. While Menger's thesis (2005), main theoretical reference, seeks to demonstrate how artists, in a certain way, have been precluding the new configurations of work in the current capitalist context - the artist as the incarnation of the worker of the future.The present thesis shows how the works in artistic fields are subordinated to the same influences of the other workers, with respect to the variable higher education. It focuses, therefore, not on what models of artistic works can predict for the other works performed socially, but on how similar are the conditions of work and the financial returns between these and those in the present time.